H. Todorova (ed.), Durankulak 3. Die hellenistischen Befunde - Şahin, Reyhan (Journal of Hellenistic Pottery and Material Culture, 2019)
This work constitutes the third volume of the excavation results in Durankulak, a site in north-eastern Bulgaria at a distance of 2.5 km from the Black Sea. The book comprises different articles related to the research on the Kybele Temple on the Big Island of Lake Durankulak. The contributions are written in German and English. Each contribution has a summary in Bulgarian at the beginning, and there is an extensive English summary at the end.